Foldback Intercoil DNA and the Mechanism of DNA Transposition - Byung-Dong Kim (Genomics & Informatics)
Foldback intercoil (FBI) DNA is formed by the folding back at one point of a non-helical parallel track of double-stranded DNA at as sharp as 180° and the intertwining of two double helixes within each other's major groove to form an intercoil with a diameter of 2.2 nm. FBI DNA has been suggested to mediate intra-molecular homologous recombination of a deletion and inversion. Inter-molecular homologous recombination, known as site-specific insertion, on the other hand, is mediated by the direct perpendicular approach of the FBI DNA tip, as the attP site, onto the target DNA, as the attB site. Transposition of DNA transposons involves the pairing of terminal inverted repeats and 5-7-bp tandem target duplication. FBI DNA configuration effectively explains simple as well as replicative transposition, along with the involvement of an enhancer element. The majority of diverse retrotransposable elements that employ a target site duplication mechanism is also suggested to follow the FBI DNA-mediated perpendicular insertion of the paired intercoil ends by non-homologous end-joining, together with gap filling. A genome-wide perspective of transposable elements in light of FBI DNA is discussed.